Design Of Evolutive Pipe Shape - Kusno, Kusno; Hidayat, Rusli; Juliyanto, Bagus (Jurusan Matematika FMIPA Universitas Jember, 2016)
We formulate evolution tube defined by Bezier dan natural curve in three steps as the following. Firstly, calculating the parametric surfaces of Bezier and natural evolution tube defined by Serret Frenet frame is done. Secondly, we formulate parametric continuity for joining the tubes. Finally, the application of those formulas for modeling the tubes by using computer are simulated.